At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To perform the binomial expansion of [tex]\((x + 2)^4\)[/tex], we will use the Binomial Theorem. The Binomial Theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
For our particular case [tex]\((x + 2)^4\)[/tex], let's set [tex]\(a = x\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(n = 4\)[/tex]. Applying the binomial theorem, we get:
[tex]\[ (x + 2)^4 = \sum_{k=0}^{4} \binom{4}{k} x^{4-k} \cdot 2^k \][/tex]
Let's break this down term by term:
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{4}{0} x^{4-0} \cdot 2^0 = 1 \cdot x^4 \cdot 1 = x^4 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{4}{1} x^{4-1} \cdot 2^1 = 4 \cdot x^3 \cdot 2 = 8x^3 \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{4}{2} x^{4-2} \cdot 2^2 = 6 \cdot x^2 \cdot 4 = 24x^2 \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{4}{3} x^{4-3} \cdot 2^3 = 4 \cdot x \cdot 8 = 32x \][/tex]
5. For [tex]\(k = 4\)[/tex]:
[tex]\[ \binom{4}{4} x^{4-4} \cdot 2^4 = 1 \cdot 1 \cdot 16 = 16 \][/tex]
Adding all these terms together, we get:
[tex]\[ x^4 + 8x^3 + 24x^2 + 32x + 16 \][/tex]
Therefore, the binomial expansion of [tex]\((x + 2)^4\)[/tex] is:
[tex]\[ x^4 + 8x^3 + 24x^2 + 32x + 16 \][/tex]
The correct answer from the given choices is:
[tex]\[ x^4 + 8x^3 + 24x^2 + 32x + 16 \][/tex]
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
For our particular case [tex]\((x + 2)^4\)[/tex], let's set [tex]\(a = x\)[/tex], [tex]\(b = 2\)[/tex], and [tex]\(n = 4\)[/tex]. Applying the binomial theorem, we get:
[tex]\[ (x + 2)^4 = \sum_{k=0}^{4} \binom{4}{k} x^{4-k} \cdot 2^k \][/tex]
Let's break this down term by term:
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{4}{0} x^{4-0} \cdot 2^0 = 1 \cdot x^4 \cdot 1 = x^4 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{4}{1} x^{4-1} \cdot 2^1 = 4 \cdot x^3 \cdot 2 = 8x^3 \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{4}{2} x^{4-2} \cdot 2^2 = 6 \cdot x^2 \cdot 4 = 24x^2 \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{4}{3} x^{4-3} \cdot 2^3 = 4 \cdot x \cdot 8 = 32x \][/tex]
5. For [tex]\(k = 4\)[/tex]:
[tex]\[ \binom{4}{4} x^{4-4} \cdot 2^4 = 1 \cdot 1 \cdot 16 = 16 \][/tex]
Adding all these terms together, we get:
[tex]\[ x^4 + 8x^3 + 24x^2 + 32x + 16 \][/tex]
Therefore, the binomial expansion of [tex]\((x + 2)^4\)[/tex] is:
[tex]\[ x^4 + 8x^3 + 24x^2 + 32x + 16 \][/tex]
The correct answer from the given choices is:
[tex]\[ x^4 + 8x^3 + 24x^2 + 32x + 16 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.